The Presence of Listeria Species in Corn Silage and Raw Milk Produced in Southeast Region of Turkey - Durmaz, Hisamettin; Avci, Mehmet; Aygun, Osman (Kafkas Univ, Veteriner Fakultesi Dergisi, 2015)
The objective of this study was to investigate the presence of Listeria species in the corn silage and raw milk samples. A total of 140 raw milk samples obtained from cows, sheeps and goats fed with silage and 90 corn silage samples collected from 10 dairy farms in South-Eastern Region of Turkey were analyzed for Listeria spp. In the result, L. monocytogenes and L. innocua were isolated from 2 (2.2%) and 5 (5.5%) silage samples and from 3 (2.1%) and 5 (3.5%) raw milk samples, respectively. The results indicates that these are a potential risk for animals and public health. Prevention of growth of L. monocytogenes in silage will also contribute to reduction of Listeria spp. in milk.
Türkiye’nin güneydoğu bölgesi’nde üretilen mısır silajı ve çiğ sütlerde listeria türlerinin varlığı
Keywords: Listeria spp.; L. monocytogenes; Raw milk; Silage